KEMAMPUAN MENGAPRESAISI PUISI DENGAN METODE HERMENEUTIK DALAM PENGUASAAN BAHASA FIGURATIF SISWA MAN 2 MATARAM TAHUN PELAJARAN 2018/2019 - Sukran Makmun; Rabiyatul Adawiyah (Balai Bahasa Nusa Tenggara Barat, 2018)
This research is aimed to determine the ability to appreciate poetry by hermeneutic methods in mastering figurative language of students of MAN 2 Mataram in 2017/2018 academic year. This research is quantitative research. The data is collected by using observation and test. The research sample is students of grade X Mia consisting of 12 students of MAN 2 Mataram. Sample is selected by employing purposive sampling technique. Data analysis used is descriptive statistics. The result shows an average value of 76.25 with a standard deviation of 6.44, so that the ability to appreciate poetry with hermeneutic methods in mastering the figurative language of students Man 2 Mataram is high.